Ureditev finančnih zavarovanj v primerljivih pravnih ureditvah - Šlamberger, Miha (Podjetje in delo, 2016)
The European Commission aimed, with Directive 2002/47/EC, to eliminate the restrictions for an efficient use of financial collateral arrangements by abolishing formal requirements for the creation and execution of financial collateral, by supporting the protection of financial collateral arrangements against statutory insolvency regulation, by introducing the right of use of given collateral and admitting the title transfer and close-out netting provisions. Financial instruments, cash and credit claims can be used as financial collateral and collateral agreements may be concluded only between designated parties being legal entities only with allowed special provisions. Special provisions are handling formal requirements for concluding financial collateral agreements (limitation of administrative burdens), the possibility of special agreements on the right of use, appropriation and close-out netting in the case of the occurrence of the enforcement event. The article deals with the legal framework for financial collateral arrangements in Austria, Germany and Great Britain.
Keywords: krediti; primerjalno pravo; terjatve; zavarovanje